The degree of preparedness and experience of student nurses participating in the generic program during their first clinical experience - Yardena Kol; Marina Vexler (Archives of Nursing Practice and Care - Peertechz Publications, 2021)
Objective: To examine the first clinical experience of student nurses from their perspective and determine the factors that influence it. Method: Sample: 103 student nurses whose first clinical experience was in internal medicine and surgical departments. Tool: a questionnaire that included demographic details, questions on the clinical training experience, and questions about factors that may affect the training experience.  Results: The factor analysis found 4 factors that explained up to 33.82% of the variance in the experience: (1) the clinical instructor's attitude toward the student, (2) the student's self-confidence in his or her abilities, (3) the department staff's attitude toward the student, and (4) a sense of calmness and familiarity with the work environment. The students' experience in each of the factors was above 4.33 on average (on a scale of 1-5). A strong, positive correlation was found between the support and guidance of the preceptor and between the clinical instructor's approach toward the student; between the support and guidance of the preceptor, a sense of confidence and ability to provide care; and between a positive relationship with staff and colleagues and the student's confidence in his or her personal ability.  Conclusion: The human factor in the training: the clinical instructor, staff, and colleagues are of the utmost importance in students' having a positive experience in their first clinical training. Highlights • Student nurses' experience in first clinical experience • Experience of student nurses in generic program • First experience of student nurses.